Relation of social and economic factors to health policy - SAVIČIŪTĖ, Rasa; JUOZULYNAS, Algirdas; JURGELĖNAS, Antanas; VENALIS, Algirdas (Acta medica Lituanica, 2012)
Health is more than just the absence of disease. Effective health systems need an efficient health policy that is formed by various factors (like environmental, genetic, social, economic, physical, etc.). The greatest challenge and major goal of health policy is to improve the health of all population, but if we want to do this it is necessary to improve the health care system so that it could work like one united system. The human being has a significant impact on health policy-making (his / her self-determination and choice). The fundamental value of health policy-making must be involvement of all citizens in the decision-making related to health policy, supervision, training / education, etc. This process has to include society, public health professionals, doctors, politicians, press, business and so on, all of them must work, make decisions and find solutions together. Close and effective communication and collaboration are necessary between all sectors and public health professionals, also it is very important to collect information, ability and skills which would help to develop and improve existing characteristics and reform health policy. In order to achieve this goal, due attention and balance must be given to various cultural, management, technical, legal, political, social and economic processes.
Keywords: health policy; social factor; economic factor; health relation